Elimination of Congenital Syphilis: What's New for Obstetricians in the 2020 Thai National Guideline? - Chenchit Chayachinda; Kittipoom Chinhiran; Surasith Chaithongwongwatthana; Rossaphorn Kittiyaowamarn; Manopchai Thamkhantho (The Royal Thai College of Obstetricians and Gynaecologists, 2020)
The goal of eliminating congenital syphilis in Thailand is to reduce new cases from 50 per 100,000 live births in 2015 to 5 per 100,000 live births in 2020. This remains a challenge because the incidence of syphilis in pregnant women is rising in many regions of Thailand. Therefore, the Ministry of Public Health of Thailand has revised the national guideline to control the situation by increasing the screening for Thai people with high risk of getting the disease; early detection and treatment of pregnant women with syphilis; suggesting pathological examination of placenta as well as identification of Treponema pallidum; enhancing the corporation between obstetricians and pediatricians; and emphasizing the post-treatment follow-up including contact tracing.